Streets & patterns : the structure of urban geometry - Marshall, Stephen, 1967- (Spon, 2005)
"Streets & patterns takes up the challenge of how to create better urban places without compromising the basic functionality of circulation and access. To tackle these issues, the book looks behind and beyond immediate policy rhetoric and design convetions, and revisits a range of first principles from a variety of disciplinary perspectives, to inform an integrative framework that may be used to underpin today's streets-oriented urban design agenda."--Page 4 of cover